Pembaruan Pendidikan Islam K.H. Hasyim Asy’ari - As'ad, Mahrus (TSAQAFAH, 2012)
The  characteristic of  the  Indonesia  Islamic  education modernism  is  largerly determined by  the  creativity which  the Muslim pointed  out. The  flexibility of   the Islamic  education  system  enable  it  to easily  adapt  itself  to  the  surrounding and  to create the new and appropriate format of  its derivation in line with the new demand of  the umma  for  the  field  in  the modern  era. A number of  experiments had been performed by the Muslim figures, individually or collectively , to fulfill that demand in the early decades of  the 20th century. How did they adopt the elements of  modernity to keep the  Islamic education  remain  in  its own  identity? For this purpose,  it  is  important to understand and  to  explain the  ideas and  the efforts of Syaikh Hasyim Asy’ari of Tebuireng in modernizing his pesantren and its main contribution to the development of   the new madrasahs  in  the  country. Using  the  analytical-critical method,  this examination is in conclusion that Hasyim’s allegiance to stand on his traditional bases in modernizing his pesantren has created a something useful for directing the orientation and giving the strong foundation of  the Indonesia’s Islamic education modernism. His success in harmonizing the elements of  modernity with the Islamic traditions under the religious inspection as the pivotal axis is his real contribution to the new madrasah with its own identity to distinct itself with the public school, though the government has “nationalized” the first to be in equivalent to the public school.